Developing Innovative Models for Learning in Social Isolation Environments: Exemplifying it for the Bone Anatomy Study - Santiago, Phellipe Caetano; Chagas, João Vitor da Silva; Conci, Aura (Proceedings of the Life Improvement in Quality by Ubiquitous Experiences Workshop (LIQUE); 2021: Proceedings of the 1st Life Improvement in Quality by Ubiquitous Experiences WorkshopDO - 10.5753/lique.2021.15717, 2021)
Anatomy knowledge is essential for many professionals, such as: doctors, nurses, biologists, biochemical, physiotherapists and any professional in physical education. Over the years, the main anatomical teaching method, the dissection of cadavers becomes less common due to issues related to high costs associated with the maintenance of laboratories, ethical aspects and health risks related to exposure to formaldehyde vapor. This factor was maximized with the Covid-19 pandemic, since presentials accesses to laboratories have become unviable. In order to offer a complementary tool for the teaching of bone anatomy, we propose in this work a serious game in augmented reality, based on controls by analysis of manual gestures, to assist the learning of this discipline.